2017
DOI: 10.1016/j.bbrc.2017.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CD36 attenuates adipogenesis with a reduction of P2X7 expression in 3T3-L1 cells

Abstract: Adipogenesis is a process of differentiation from preadipocyte into adipocyte, and is regulated by several transcription factors, including the peroxisome proliferator-activated receptor gamma (PPARγ) and the CCAAT-enhancer-binding protein alpha (C/EBPα). CD36 is a membrane protein which contributes to the metabolic disorders such as obesity. Although the previous study demonstrated CD36 participated in the progression of adipogenesis, the mechanism is still unclear. We report here that knockdown of CD36 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
(22 reference statements)
2
23
0
Order By: Relevance
“…Accordingly, proliferation rates of murine fibroblasts are not only determined by their age and fibroblast lineage identity but also by the dermal composition (Lichtenberger et al, 2016).Thus, functional heterogeneity of distinct fibroblast subsets is defined by both their identity and microenvironment. For example, CD36 expression is higher in the lower dermis where adipogenesis occurs, which is coherent with its reported function (Gao et al, 2017a(Gao et al, , 2017b. Dermal microvascular endothelial cells also display heterogeneous CD36 expression depending on their localization within the dermis (Petzelbauer et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Accordingly, proliferation rates of murine fibroblasts are not only determined by their age and fibroblast lineage identity but also by the dermal composition (Lichtenberger et al, 2016).Thus, functional heterogeneity of distinct fibroblast subsets is defined by both their identity and microenvironment. For example, CD36 expression is higher in the lower dermis where adipogenesis occurs, which is coherent with its reported function (Gao et al, 2017a(Gao et al, , 2017b. Dermal microvascular endothelial cells also display heterogeneous CD36 expression depending on their localization within the dermis (Petzelbauer et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
“…FAP þ CD90 þ also expressed high levels of COL11A1 and FMO1 (Figure 2e, and see Supplementary Figure S1g). Both FAP e CD90 þ and FAP þ CD90 þ fibroblasts displayed high expression levels of CD36 and PPARg, both of which are involved in fatty acid metabolism and adipogenesis (Gao et al, 2017a(Gao et al, , 2017bSiersbaek et al, 2010). These findings indicate that while FAP þ CD90 e cells represent papillary fibroblasts, FAP e CD90 þ cells depict reticular fibroblasts.…”
Section: Isolation Of Functionally Distinct Papillary and Reticular Fmentioning
confidence: 88%
See 1 more Smart Citation
“…Oil Red O staining. In brief, following fixation of the mature adipocytes in 10% (v/v) formaldehyde solution for 30 minutes, the cells were stained with 0.5% Oil Red O for 30 minutes at room temperature, rinsed in PBS, as previously described (49).…”
Section: Discussionmentioning
confidence: 99%
“…In 3T3-L1 pre-adipocytes, the extracellular ATP has been demonstrated to regulate hormone-induced adipocyte differentiation, which is mediated by P2Y receptors without affects pre-adipocyte proliferation [111]. It has been recently reported that knockdown of CD36, a membrane protein that has been demonstrated to participate in the progression of adipogenesis, resulted in a reduction of adipocyte differentiation and downregulation of purinergic receptor P2X7 expression, suggesting that the suppression of adipogenesis mediated by CD36 is probably via P2X7 pathway in 3T3-L1 cells [112]. Although P2 receptors have been proved to play a role in adipogenesis, the underlying mechanisms are still needed for further investigation.…”
Section: P2 Receptors In Adipogenesismentioning
confidence: 99%